The Effectiveness of Community-Based Sanitation Programs in Langkat Regency - Ilhamsyah Bangun; Abdi Sugiarto; Cut Nuraini (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
The Community-Based Sanitation Program (PAMSIMAS) is a government initiative aimed at improving community access to proper sanitation facilities, particularly in rural areas. This study aims to evaluate the effectiveness of the program in Tanjung Aman Village, Wampu District, Langkat Regency. A qualitative approach was used with a phenomenological method, focusing on the experiences and perceptions of local residents and village officials regarding program implementation. Data were collected through in-depth interviews, field observations, and documentation, involving 15 informants comprising residents, sanitation cadres, and village officials. The findings show that technically, the sanitation facilities function well; however, sustainability in usage faces challenges such as low community participation, weak maintenance systems, and the absence of binding local regulations. Community perception of the program is generally positive, particularly regarding improvements in environmental cleanliness and comfort in using the facilities, yet unequal access remains a significant issue. The study concludes that the success of PAMSIMAS largely depends on collaboration among the community, local cadres, and village policies. Strategic recommendations include the formulation of Village Regulations, regular training for cadres, and the establishment of a community-based sanitation management institution. With this approach, the program is expected to operate sustainably and provide long-term benefits to rural communities.